Hepatectomia videolaparoscópica. Experiência pessoal com 107 casos - Machado, Marcel Autran Cesar [UNESP]; Makdissi, Fábio Ferrari [UNESP]; Surjan, Rodrigo Cañada Trofo [UNESP] (FapUNIFESP (SciELO), 2012)
Objective: To analyze our experience after 107 laparoscopic hepatectomies and discuss the technical evolution of laparoscopic hepatectomy in the last five years. Methods: Between April 2007 and April 2012 we performed 107 laparoscopic hepatectomies in 105 patients. The mean age was 53.9 years (17 to 85). Fifty-three patients were male. All interventions were performed by the authors. Results: from the total of 107 operations, there was need for conversion to open technique in three cases (2.8%). Sixteen patients (14.9%) had complications. Two patients died, a mortality of 1.87%. One death was due to massive myocardial infarction, unrelated to the procedure, which was uneventful and showed no conversion or bleeding. The other death was due to failure of the stapler. Twenty patients (18.7%) required blood transfusion. The most frequent type of hepatectomy was bisegmentectomy of segments 2-3, (33 cases), followed by right hepatectomy (22 cases). Seventy-two procedures (67.3%) were performed by the technique of Glissonian access. Conclusion: The dissemination of results is of utmost importance. The technical difficulties, complications and even death, inherent in this complex type of surgery, need to be clearly disclosed. This procedure should be performed in a specialized center with knowledgeable staff. The technique of laparoscopic Glissonian access, described by our staff, facilitates the realization of anatomical hepatectomies.
Laparoscopic liver resection. Personal experience with 107 cases
Keywords: General surgery; Hepatectomy; Laparoscopy; Liver; Techniques